Development of Interactive e-Modules on Integrated Learning Model Materials of Moderation Values Religious - Mimi Herman; Hidayat Herman (Universitas Lampung, 2022)
Abstract : Title is rewritten here Development of Interactive E-Modules on Integrated Learning Model Materials of Moderation Values Religious. The diversity of tribes, languages, cultures, and religions owned by Indonesia should become a treasure trove of the nation's wealth. However, recently this diversity has become a trigger for disharmony, especially when it is associated with religion. Problems of religious disharmony such as intolerance also occur in educational institutions. Examples of intolerance are the spread of false news (hoaxes) and increased persecution among high school students, bullying and the emergence of differences based on religion, ethnicity, and others are forms of intolerance. One way to overcome this is to integrate the values of religious moderation in the lecture process through learning media. Therefore, the aim of this study was to produce an e-module learning model in the Chemistry Learning Strategy course integrated with religious moderation values that are valid and practical. The research method used is Research and Development with a 4D model. The object of this research is students in the fourth semester of the Department of Tadris Chemistry at UIN Mahmud Yunus Batusangkar. The results of this study indicate that the language validity value of the e-module is 0.89 with a very high validity category, material validity is 0.76 high validity category, and construct validity value is 0.76 high validity category. The results of the practicality test according to students were 0.89 in the very high practicality category. Based on these findings it can be concluded that the e-module learning model in the Chemistry Learning Strategy course integrated with religious moderation values is very valid and very practical to use in the lecture process. Keywords: religious moderation values, e-modul, learning models.